Positional Advantages, Consumer Preferences for Indonesian National Rice SPHP VS Local Rice, And Dynamic Marketing Capabilities on Marketing Performance : a Case Study on the West Kalimantan Provincial Government’s Cheap Food Movement - Hendra, Hendra; Venebis, Venebis; Nurcholis, Lutfi (Syntax Literate, 2025)
This mixed-method study investigates consumer choice between nationally subsidized rice (SPHP) and local rice in the West Kalimantan Cheap Food Movement (GPM) program. This study examines positional advantage and dynamic marketing ability. Quantitative findings indicate the price and availability advantages of SPHP rice. Qualitative data reveal consumer perceptions of the quality of local rice. This study concludes with implications for food security programs."This mixed-methods study rigorously investigates the intricate interplay between positional advantage, consumer choice dynamics concerning the Stabilisasi Harga Pangan dan Ketersediaan Pangan (SPHP) national rice program versus locally sourced rice, the role of dynamic marketing capability, and the resultant marketing performance within the specific socio-economic context of the Gerakan Pangan Murah (GPM) initiative implemented by the Food Security Agency of West Kalimantan Province. Employing a sequential explanatory design, the study first quantifies consumer perceptions of positional advantages and their rice preferences through a survey of 200 GPM participants, utilizing random sampling and analyzed via descriptive statistics and regression analysis. Subsequently, qualitative insights are gathered through in-depth interviews with 20 consumers and 5 program managers, selected via purposive sampling, and focus group discussions to deeply explore the underlying motivations behind consumer choices and the strategic deployment of dynamic marketing capabilities. The quantitative findings reveal a significant consumer perception of SPHP rice's positional advantage, particularly in terms of price and consistent availability. The qualitative data further elucidates that affordability and accessibility are primary drivers for SPHP rice preference, while also uncovering nuances related to local rice quality perceptions and marketing efforts. This research contributes to a more nuanced understanding of agricultural marketing strategies within the context of national food security programs, consumer behavior in developing economies, and the strategic importance of dynamic marketing capabilities in achieving program objectives. The findings offer practical implications for policymakers and marketing practitioners seeking to enhance the effectiveness and sustainability of food security initiatives